Serious generalized pustular psoriasis with evolution to plaque psoriasis: approach with spesolimab - Liz S. Gea; Julia C. K. El Dib; Omar Algazal; Eduardo C.N. Constantino; Vera L. A. Nasser; João R. Antonio (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Generalized pustular psoriasis (GPP) is characterized by an acute and severe variant of psoriasis, often accompanied by systemic symptoms, with the eruption of multiple sterile pustules over an area of erythema, associated or not with the form of plaque psoriasis. Epidemiological data on disease are limited, but a global prevalence is estimated at around 1-7 cases per million people, affecting mainly females, with a higher incidence in the fourth and fifth decades of life. Exacerbations are marked by varying degrees of inflammation and systemic symptoms and have an unpredictable evolution. Hyperactivity of the interleukin-36 (IL-36) inflammatory pathway was discovered as the main pathway responsible for causing the disease. Recently, the active substance spesolimab has shown excellent results in the treatment of GPP, with a mechanism of blocking IL-36 receptor activation, leading to the suppression of pro-inflammatory and profibrotic pathways in inflammatory skin and intestinal diseases.